A writer's reference - Diana Hacker (Bedford/St. Martins, 2007)
A Writer's Reference is the most widely adopted college handbook ever published. The new edition is available in a classic version that provides more help with academic writing, serves a wider range of multilingual students, and lends more support for college research all in an easy-to-use quick-reference format. Now for all the ways you teach your course, you can choose the classic version or choose from among 4 additional versions with varied content